Self-locking and Efficiency Maximization Design of a 3K-H Planetary Gear Train - Huang Junpeng; Kong Jianyi; Sun Wei; Xing Xing'ao; Li Baoyi (Jixie chuandong)
Planetary gear train is mainly used for power transmission, so it is of great significance to study its self-locking and efficiency. In this study, the self-locking analysis and efficiency maximization design of a 3K-H planetary gear train are carried out. Firstly, the efficiency of the positive and negative mechanism of the gear train is calculated using the transmission ratio method. Then, a unified formula for the efficiency of the planetary gear train is summarized. Furthermore, the efficiency curve is drawn by Matlab. Next, the trend of efficiency change of the planetary gear train and the conditions for realizing self-locking are analyzed. Finally, how to maximize the efficiency of the opposite mechanism under the condition of self-locking is studied.